Poster design and its role in drug control (Al-Academy, 2021)
Our dear country faces many and varied challenges aimed at its history, civilization, its people, the scourge of drugs and psychotropic substances and their misuse. Therefore, we have a historical, ethical and professional responsibility to coordinate efforts and cooperation between all concerned to protect the Iraqi society from the threat of this scourge. Creative sources have varied in the variety of expressive means in politics, literature and the arts, in their style and technical treatment of various topics with innovative manifestations and intuitive interactive with visions as well as influences Psychological expressive descriptions of visual scene, it is one of the media and propaganda that contribute to the raising and development of political and intellectual awareness of the recipient because of its power to address the minds and souls of various levels expressive and aesthetic, social, artistic and intellectual that revealed the achievement of psychological significance through form, color and importance To achieve the direct excitement and sensitivity of the recipient's sensory perceptions, and to stimulate his awareness in delivering the content of the advertising message as one of the most important media and propaganda, as it contributes to the raising and development of political and intellectual awareness A citizen's awareness, as an epistemological and emotion connotation of identity Existence based on the composition in the realistic formulation of the situation, , the harmonization of form and content and stylistic and technical processing in loading the descriptive moment expressive forms with inflammatory, guiding and educational objectives for the recipients ... The most important findings and recommendations of the research Initiation of the idea was a clear method chosen to deliver the media message without linguistic or visual obstacles 1-the convergence of content as guidance and guidance in the poster a clear expression of the weakness of design visions.. 2-Lack of use of typographical vocabulary (such as image, drawing, color, writing) and limited ideas in designing innovative ideas3-The recommendations were followed by Try to provide design ideas with meanings and indications of health, religious or national expresses the reality of Iraqi society and methods away from the complexity and exaggerated formalism1-Innovate ways to deepen the relationship between form and meaning in the design of the poster in terms of benefiting from the human community activity that is enjoyed by people around the world